Optimization of high-k composite dielectric materials of variable oxide thickness tunnel barrier for nonvolatile memory - Farah A.Hamid; Afiq Hamzah; N. Ezaila Alias; Razali Ismail (Institute of Advanced Engineering and Science, 2019)
Downscaling the tunnel oxide thickness has become one of the innovative solutions to minimize the operational voltage with better the programming/erasing (P/E) operation time. However, the downscaling technique faces several challenges where the conventional SiO2 tunnel layer has reached its limit. But a practical alternative has been introduced; Variable Oxide Thickness (VARIOT) technology in flash memory has been promising. VARIOT is one of tunnel barrier engineering technology for incorporating the high-k dielectric materials as a composite tunnel barrier. This paper presents the VARIOT concept to determine the optimum set of combination, the equivalent oxide thickness (EOT) and the low-k oxide thickness (Tox) for alternate high-k materials. Fowler-Nordheim (F-N) tunneling coefficients are also extracted for various combinations of VARIOT, where in this work ZrO2, HfO2, Al2O3, La2O3, and Y2O3 are used. The VARIOT optimization is conducted using 3-Dimensional (3D) Silicon Nanowire Field-Effect-Transistor (SiNWFET) device structure and simulated in TCAD Simulation tools. From the simulation results, it has found out that the high-k materials of La2O3 asymmetric stack is the excellent dielectric material among four (4) other dielectric materials; ZrO2, HfO2, Al2O3 and Y2O3 for EOT=4nm and Tox=1nm.